Presence of Candida tropicalis in commercial ‘açaí’ (Euterpe oleracea Mart. ) pulps from Rio de Janeiro - Peixoto, Jaqueline Carvalho; Teixeira, Andréa Bittencourt de Santana; Neufeld, Paulo Murilo; Carvalho, Lucia Maria Jaeger de; Moura, Mirian Ribeiro Leite (MAGISTRA, 2017)
Abstract: Microbial analysis of fruit pulps is important to guarantee their sanitary quality. Increasing „açai‟ pulp consumption has led to its industrialization and its quality is monitored by Brazilian legislation with the objective of reducing the contamination risk in population. This study evaluated the microbiological quality of commercial „açaí‟ pulps consumed in Rio de Janeiro city to verify if their sanitary conditions were in compliance with Brazilian food legislation. In this work the analysis of moisture and pH were carried out and for the 30 samples of frozen and pasteurized „açaí‟ pulps the following microbiological analysis were performed: determination of the most probable number of total and fecal coliforms, Salmonella spp. yeasts and molds count. Most of the samples (70%) presented high moisture and therefore, low total solids content which represents a potential risk of contamination by microorganisms. The microbiological results revealed that the heat treatment eliminated the bacterial growth in pulps. Candida tropicalis (46.5%) was found in some samples although below the limit established by legislation. However, it may represent a risk if these „açai‟ pulps are offered as part of the diet to hospitalized patients or immunocompromised, suggesting greater rigor in quality control during manufacturing, storage and transport of frozen „açaí‟ pulps to ensure food safety. Keywords: açaí, food safety, molds, yeast, health